The outcomes of refractory glaucoma surgery using collagen bio-implant - M. M. Bikbov; V. K. Surkova; I. I. Khusnitdinov; O. I. Orenburkina; O. V. Сhayka (Oftalʹmologiâ, 2014)
Aim. To analyze the efficacy of Ologen® Collagen Matrix Implant in refractory glaucoma surgery.Materials and methods. Classical non-penetrating deep sclerectomy (NPDS) with Ologen® implantation in the scleral bed was performed.Results. Post-op, implant was visualized underneath the conjunctiva and moved within the scleral flap. Implant was resolved in 3 months with moderate filtering bleb formation. Following 12 months, visual acuity and visual fields were stable, IOP level was 12‑17 mm Hg.Conclusion. Within 12‑months follow-up, Ologen® implantation in the course of glaucoma surgery prevents scleral conjunctival scarring, provides long-term IOP-lowering effect and preserves residual visual functions.